If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9h + -27 = 36 Reorder the terms: -27 + 9h = 36 Solving -27 + 9h = 36 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + 9h = 36 + 27 Combine like terms: -27 + 27 = 0 0 + 9h = 36 + 27 9h = 36 + 27 Combine like terms: 36 + 27 = 63 9h = 63 Divide each side by '9'. h = 7 Simplifying h = 7
| 4/5x5/16 | | -5b+7-4b-2-b=-15 | | 4(3+4)-3=25 | | 2x+20=94 | | 5a+9b=360 | | 4/3T=-36 | | 4(3+4x)=25 | | 4c-8=5c+15 | | (x-7)(x+3)=24 | | 10p-7=24 | | -11.4-m=10.9 | | 20p-7=24 | | 37+(9x-1)=90 | | 3x/4-2/3=5/6 | | (3y+7)(-4x+2)= | | (6x^2+7)-(-4y^2+7)= | | 6x+15=64 | | sinx=73 | | (x+1)(10x)=(12x+2)x | | (6x+36)=(2x-5) | | 30=-3(-6-2z) | | -9x-22=-184 | | 6w^4+w^3-3w^2=0 | | 56+(7x-1)=90 | | (15/8)=((17-x)/x) | | 5n(4n+1)=0 | | 16+5a=31 | | 10x-6/3-5x | | 32-66= | | x-34=5x+2 | | (2x+6)+(5x+6)= | | 2x(-33)= |